High Alpha-pulp from Wattle (Acacia mollissima Willd.) by Water Pre Hydrolysis Sulphate Process - Singh, Man Mohan (Indian Forester, 1967)
High alpha cellulose pulps have been prepared from Acacia mollissimaWilld by waterperhydrolysis sulphate process followed by multl-stage bleaching process.The pulps could be considered for preparing various cellulose derivatives like viscose rayon, nitro cellulose, cel1ulose acetate, etc., provided these pulps pass further tests required.